1992
DOI: 10.1152/jappl.1992.72.2.575
|View full text |Cite
|
Sign up to set email alerts
|

Volume infusion produces abdominal distension, lung compression, and chest wall stiffening in pigs

Abstract: The effect of severe generalized edema on respiratory system mechanics is not well described. We measured airway pressure, gastric pressure, and four vertical pleural pressures in 13 anesthetized paralyzed pigs ventilated in the upright position. Pressure-volume relationships of the respiratory system, chest wall, and lung were measured on deflation from total lung capacity to residual volume and during tidal breathing both before (control) and 50 min after one of two interventions. In one series of experiment… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

2
64
0
8

Year Published

2014
2014
2023
2023

Publication Types

Select...
5
4

Relationship

0
9

Authors

Journals

citations
Cited by 107 publications
(74 citation statements)
references
References 0 publications
2
64
0
8
Order By: Relevance
“…This technique has some advantages over existing models. Intraperitoneal fluid infusion is likely to be absorbed and therefore may interfere with the pathophysiological response to IAH [10], while the use of CO 2 insufflation may represent an additional physiologic variable [8]. Furthermore, CO 2 may be absorbed and the gas volume can be compressed, whereas saline and cotton dressings cannot.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…This technique has some advantages over existing models. Intraperitoneal fluid infusion is likely to be absorbed and therefore may interfere with the pathophysiological response to IAH [10], while the use of CO 2 insufflation may represent an additional physiologic variable [8]. Furthermore, CO 2 may be absorbed and the gas volume can be compressed, whereas saline and cotton dressings cannot.…”
Section: Discussionmentioning
confidence: 99%
“…Although experimental models of IAH were developed using CO 2 insufflation, it is difficult to maintain high IAP levels for prolonged periods [8]. To address this issue, some authors have suggested the use of peritoneal saline infusion [9], rather than CO 2 insufflation to generate a lengthy IAH model [10]. Since the peritoneal membrane is an efficient system for drainage and absorption of liquids in the abdominal cavity, this system has also failed to maintain a stable IAP.…”
mentioning
confidence: 99%
“…However, at very low lung volumes, irrespective of body positioning, P pl may exceed atmospheric pressure (i.e., becoming positive) in the dependent regions, as the elastic recoil of the lung is smaller at lower volumes and the dependent parenchyma tends to be compressed [46]. This event is even more relevant in ARDS patients, in which the wet and edematous lungs are heavier and the gravitational gradient in pleural pressure is steeper [45,47]. This vertical gradient of P pl is clinically significant as it determines a gradient of P TP and, therefore, also of the lung ventilation.…”
Section: Interpreting P Eso Measurementmentioning
confidence: 99%
“…69 In ACS, there is actually an increase in chest wall elastance which for a given applied airway pressure results in a lower distending force of the lung, the transpulmonary pressure (i.e P Alveolar -P Pleural ). This is accompanied by a higher pleural pressure with less lung distension, 70,71 a decreased respiratory system compliance and a rightward shift of the compliance (Pressure/Volume) curve. 72 In ventilated patients with IAH, the diaphragm moves upwards statically causing lower lobe compression; an effect which is exaggerated if the patient is obese.…”
Section: Respiratory System Dynamicsmentioning
confidence: 99%